WOMEN’S ENTREPRENEURSHIP: AN EXAMINATION OF GOVERNMENT SUPPORT AND THE ROLE OF KNOWLEDGE SKILLS - Silvy Sondari Gadzali; Muhammad Ade Kurnia Harahap; Ira Modifa Tarigan; Abdullah Akhyar Nasution; Abu Muna Almaududi Ausat (Universitas Pahlawan Tuanku Tambusai, 2023)
In recent years the study of women’s entrepreneurship has seen a growth, especially during the pandemic and its aftermath. According to the literature women can make a significant contribution to entrepreneurial activity. This research aims to provide evidence that government support factors can create women's entrepreneurship. Not only that, the author will also add literature on knowledge skills in fostering the entrepreneurial spirit for women. This research includes library research, because the research is conducted to search, analyze, make interpretations and generalizations from the facts of the results of thoughts and ideas written by entrepreneurship experts. This research is descriptive qualitative with a secondary data analysis approach. This study found that the government has a crucial role in creating women's entrepreneurship both before and after the pandemic. On the other hand, the knowledge skill aspect is a supporting factor for women's success in starting a career as an entrepreneur. This research is expected to enrich both formal and informal entrepreneurship literature.